The Control of Stored Product Insect Pests With Special Emphasis on Indian Meal Moth in Dried Flower Arrangement Materials and Crafts - Bauernfeind, Robert J. (My University, 1995)
This publication describes how to control pests in stored products with dried flowers.
MF2117_1995_05
Keywords: MF2117; Insects; MF